Modulation of the Fanconi anemia pathway via chemically induced changes in chromatin structure - Vierra, David A. (Oncotarget, 2017)
Fanconi anemia (FA) is a rare disease characterized by congenital defects, bone marrow failure, and atypically early-onset cancers. The FA proteins function cooperatively to repair DNA interstrand crosslinks. A major step in the activation of the pathway is the monoubiquitination of the FANCD2 and FANCI proteins, and their recruitment to chromatin-associated nuclear foci. The regulation and function of FANCD2 and FANCI, however, is poorly understood. In addition, how chromatin state impacts pathway activation is also unknown. In this study, we have examined the influence of chromatin state on the activation of the FA pathway. We describe potent activation of FANCD2 and FANCI monoubiquitination and nuclear foci formation following treatment of cells with the histone methyltransferase inhibitor BRD4770. BRD4770-induced activation of the pathway does not occur via the direct induction of DNA damage or via the inhibition of the G9a histone methyltransferase, a mechanism previously proposed for this molecule. Instead, we show that BRD4770-inducible FANCD2 and FANCI monoubiquitination and nuclear foci formation may be a consequence of inhibition of the PRC2/EZH2 chromatin-modifying complex. In addition, we show that inhibition of the class I and II histone deacetylases leads to attenuated FANCD2 and FANCI monoubiquitination and nuclear foci formation. Our studies establish that chromatin state is a major determinant of the activation of the FA pathway and suggest an important role for the PRC2/EZH2 complex in the regulation of this critical tumor suppressor pathway.